2020
DOI: 10.1017/s0016756819001493
|View full text |Cite
|
Sign up to set email alerts
|

A Late Cretaceous felsic magmatic suite from the Tengchong Block, western Yunnan: integrated geochemical and isotopic investigation and implications for Sn mineralization

Abstract: The Tengchong Block within the Sanjiang Tethys belt in the southeastern part of the Tibetan plateau experienced a widespread intrusion of a felsic magmatic suite of granites in its central domain during Late Cretaceous times. Here, we investigate the Guyong and Xiaolonghe plutons from this suite in terms of their petrological, geochemical, and Sr–Nd, zircon U–Pb and Lu–Hf–O isotopic features to gain insights into the evolution of the Neo-Tethys. The Guyong pluton (76 Ma) is composed of metaluminous monzogranit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 88 publications
(175 reference statements)
1
14
0
Order By: Relevance
“…The Lailishan monzogranites and syenogranites contain relatively high Sn contents (6.08–49.50 ppm), which are similar with those of Sn specialized granites (Sn ≥15; Neiva, 1984) and the Sn‐bearing Xiaolonghe granites in Tengchong Block (8.14–20.2 ppm; Sun et al, 2020), instead of normal granites without Sn mineralization (4.3 ppm; Tischendorf, 1977). Hence, the granitic melts produced by the partial melting of the ancient crustal basement from the Tengchong Block are enriched in Sn, and the crystallization differentiation of silicate melts made the residual melts fertile and generated volatiles through exsolution (Halter & Webster, 2004; Lehmann, 1990).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The Lailishan monzogranites and syenogranites contain relatively high Sn contents (6.08–49.50 ppm), which are similar with those of Sn specialized granites (Sn ≥15; Neiva, 1984) and the Sn‐bearing Xiaolonghe granites in Tengchong Block (8.14–20.2 ppm; Sun et al, 2020), instead of normal granites without Sn mineralization (4.3 ppm; Tischendorf, 1977). Hence, the granitic melts produced by the partial melting of the ancient crustal basement from the Tengchong Block are enriched in Sn, and the crystallization differentiation of silicate melts made the residual melts fertile and generated volatiles through exsolution (Halter & Webster, 2004; Lehmann, 1990).…”
Section: Discussionmentioning
confidence: 90%
“…The Late Cretaceous granites (Xiaolonghe and Yunfengshan) were mainly emplaced during 76–68 Ma (Figure 1b; Jiang, Gong, Zhang, & Ma, 2012; Ma et al, 2013; Xu et al, 2012). The Xiaolonghe tin deposit is associated with the Late Cretaceous fine‐grained syenogranite in the Xiaolonghe granite unit (76 Ma;Sun et al, 2020). The Early Tertiary granites consist of the Xinqi, Lailishan, and Baihuanao granitic units, and exhibit zircon U–Pb ages ranging from 66 to 52 Ma (Booth et al, 2004; Liang et al, 2008; Chiu et al, 2009; Xie et al, 2010;Xu et al, 2012).…”
Section: Regional Geologymentioning
confidence: 99%
“…The fractional crystallization of K‐feldspar could reduce the Ba and Eu content in the melt without affecting other trace elements (Zhu et al, 2020); therefore, the decreasing Ba and Eu contents from ASs to FSs also confirmed the fractional crystallization of K‐feldspar. In addition, the ratios of the trace elements such as Rb/Sr, Rb/Ba and Nb/Ta are good indicators to evaluate the degree of fractional crystallization (Sun et al, 2020). As shown in Figure 13, the increase in Rb/Sr and Rb/Ba ratios and the decrease in Ba content from ASs to FSs, suggesting fractional crystallization of K‐feldspar and biotite.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the magmatism in Tengchong Block shows a western younging trend and can be divided into three granite belts (Z. Sun et al, 2020): the Early Cretaceous Donghe granite belt in the eastern Tengchong Block, the Late Cretaceous Guyong granite belt in the middle Tengchong Block, and the Palaeogene Binglangjiang granite belt in the western Tengchong Block (Figure 1b).…”
Section: Geological Setting and Petrographymentioning
confidence: 99%
“…The Tengchong Block in SW China hosts abundant Mesozoic-Cenozoic granitoids with various compositions, recording complex processes of magmatic evolution (Z. Sun et al, 2020;Xie et al, 2016).…”
mentioning
confidence: 99%